Mixotrophic cultivation of Chlorella vulgaris using industrial dairy waste as organic carbon source - Abreu, Ana P.; Fernandes, Bruno; Vicente, António A.; Teixeira, José; Dragone, Giuliano (Bioresource technology, 2012)
► Cheese whey was used as carbon source for Chlorella vulgaris growth. ► Mixotrophic microalgae grew faster than photoautotrophic cells. ► Maximum starch productivity was achieved under mixotrophic conditions. ► Highest pigment content (0.74%) was obtained in the photoautotrophic culture. Growth parameters and biochemical composition of the green microalga Chlorella vulgaris cultivated under different mixotrophic conditions were determined and compared to those obtained from a photoautotrophic control culture. Mixotrophic microalgae showed higher specific growth rate, final biomass concentration and productivities of lipids, starch and proteins than microalgae cultivated under photoautotrophic conditions. Moreover, supplementation of the inorganic culture medium with hydrolyzed cheese whey powder solution led to a significant improvement in microalgal biomass production and carbohydrate utilization when compared with the culture enriched with a mixture of pure glucose and galactose, due to the presence of growth promoting nutrients in cheese whey. Mixotrophic cultivation of C. vulgaris using the main dairy industry by-product could be considered a feasible alternative to reduce the costs of microalgal biomass production, since it does not require the addition of expensive carbohydrates to the culture medium.